Actor-network theory as a methodology of modern social research - Mozalevskaya, Daniela A. (Journal of the Belarusian State University. Philosophy and Psychology, 2022)
The article presents an investigation of the actor-network theory (ANT) and its conceptual contribution to the understanding of changes in modern society. The key concepts and methodological principles of ANT are defined, such as generalised symmetry, flat ontology, demonstrating the complexity of the social world and a new hybrid understanding of reality. The characteristic features of ANT are revealed, including its emphasis on the inseparability of human and non-human factors in hybrid networks. The categorical apparatus of this program and the process of translation are considered. Critical remarks on the ANT are given and the heuristic potential of the theoretical approach in the context of interdisciplinary research is presented.
Keywords: actor-network theory; actor – network; concept of generalised symmetry; process of translation; concept of flat ontology